Clinical outcomes in patients with muscle disorders and acute ischemic stroke - Adeel S. Zubair; Lauren Littig; Daniel B. DiCapua; Adam de Havenon (PLoS ONE, 2025)
Objectives Stroke is a leading cause of morbidity in the United States, which prompts an exploration into its associated risk factors. Muscle disorders have been linked to an increased risk of stroke; however, research on stroke prevalence and clinical outcomes in this population is limited by small sample sizes. Although the diagnostic and treatment protocols for acute ischemic stroke are largely identical in patients with and without muscle disorders, it remains unclear whether clinical outcomes differ. This study aimed to address this gap using a large, nationally representative dataset. Materials and methods We conducted a retrospective analysis of the 2016–2022 National Inpatient Sample to compare clinical outcomes in patients with and without muscle disorders hospitalized for an acute ischemic stroke. Results Patients with pre-existing muscle disorders had significantly higher rates of intubation, PEG tube placement, and in-hospital mortality, as well as a lower likelihood of discharge to home, compared to those without muscle disorders. Conclusions These findings suggest that patients with muscle disorders experience worse outcomes following an ischemic stroke. Further research is needed to identify the underlying factors driving these disparities and to inform targeted strategies for improving outcomes in this vulnerable population.